Charity and Justice: A Conversation with Evangelical Christian Women Serving Marginalized Populations in British Columbia. (30th November 2017) - Chan, Kathryn; Thrift, Erin
Abstract : This exploratory study examines how a group of evangelical Christian women are seeking to define and live out the concepts of charity and justice in the contexts of their work with marginalized populations in British Columbia. The authors identify several themes that emerged in conversation with participants. These themes include the complex relationship between justice and charity, the effects of charity's "social architecture", and the relationship between justice/ charity and gender.